2013
DOI: 10.1155/2013/256508
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of PPARs in Placenta

Abstract: Peroxisome proliferator-activated receptors (PPAR) are members of the superfamily of nuclear hormone receptors involved in embryonic development and differentiation of several tissues including placenta, which respond to specific ligands such as polyunsaturated fatty acids by altering gene expression. Three subtypes of this receptor have been discovered, each evolving to achieve different biological functions. The PPARs also control a variety of target genes involved in lipid homeostasis. Similar to other nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Abnormal trophoblast differentiation and function are the bases for development of preeclampsia, and trophoblast cells appear to be the source of production of proinflammatory cytokines 42 . PPAR‐γ is highly expressed in human placenta, predominantly in trophoblasts, and appears to play a role in trophoblast differentiation 43 . PPAR‐γ knockout mouse models have shown placental defects and fetal loss in early pregnancy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal trophoblast differentiation and function are the bases for development of preeclampsia, and trophoblast cells appear to be the source of production of proinflammatory cytokines 42 . PPAR‐γ is highly expressed in human placenta, predominantly in trophoblasts, and appears to play a role in trophoblast differentiation 43 . PPAR‐γ knockout mouse models have shown placental defects and fetal loss in early pregnancy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…PINK1 mutations are the most common cause of recessive familial Parkinsonism in humans . In addition, PINK1 KO mice exhibits severe deficiencies in mitochondrial homeostasis accompanied by morphological changes in the mitochondrial network, increased ROS, and susceptibility to heat shock . Together this evidence suggests defective mitophagy plays an important role in Parkinson's disease as well as overall mitochondrial quality in healthy cells and suggests an important role in aging.…”
Section: Mitophagymentioning
confidence: 95%
“…Two well characterized regulators of mitophagy are PINK1 and parkin . PINK1, aka phosphatase and tensin (PTEN) homologue‐induced kinase 1, is a mitochondria‐targeted serine/threonine kinase which serves to protect the cell from mitochondrial dysfunction and apoptosis . PINK1 mutations are the most common cause of recessive familial Parkinsonism in humans .…”
Section: Mitophagymentioning
confidence: 99%
“…It has been reported that regulation of PPARα expression and activity contributes to maintaining a homeostatic balance between cellular fatty acid and glucose utilization via activation of its target genes (11). Accordingly, activation of PPARα increases sensitivity to insulin as well as thrombosis and vascular inflammation (18)(19)(20). By contrast, it appears that inhibition of PPARα suppresses sensitivity to insulin and increases hepatic glucose production.…”
Section: Expression Of Luciferase Gene With Mutated or Wild-type Pparmentioning
confidence: 99%